2018
DOI: 10.1209/0295-5075/121/24002
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic flow actuation using magnetoactive suspensions

Abstract: The rheological behavior of magnetotactic bacterial suspensions is analyzed using a continuum kinetic theory. In both unbounded and confined geometries, the response of these suspensions under simple external flows can be controlled by applying a magnetic field and hinges in a subtle way on the interplay of magnetic alignment, rotation under shear, and wall-induced accumulation under confinement. By tuning magnetic field strength and direction, the apparent viscosity can either be enhanced or reduced, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…For example, the magnetic alignment, combined with a micro-aerotactic swimming response, qualifies such micro-swimmers as a promising vector for targeted drug therapy [32]. Recently, it was proposed, on theoretical grounds, that a suspension of such magnetotactic bacteria could display original magneto-rheological properties [33,34], novel pattern formation [35] and hydrodynamic instabilities [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the magnetic alignment, combined with a micro-aerotactic swimming response, qualifies such micro-swimmers as a promising vector for targeted drug therapy [32]. Recently, it was proposed, on theoretical grounds, that a suspension of such magnetotactic bacteria could display original magneto-rheological properties [33,34], novel pattern formation [35] and hydrodynamic instabilities [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically it is shown that MTB might present original magnetorheological properties and present novel collective behavior. [ 378–381 ] Experimentally, the MTB were shown to behave as rotary motors in oil–water emulsions for example and therefore their behavior in complex medium is an open field. [ 382 ] In this line, taking into account that among MTB strains they have different properties and needs, the same diversity is most likely to be translated to different collective behaviors which if controllable are of interest for the field or robotics.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Colloidal suspensions of microscopic particles show complex and interesting collective behaviors. In particular, the collective dynamics of colloids is fundamental and ubiquitous for materials assembly [ 1 , 2 ], robotic motion [ 3 , 4 ], microfluidic control [ 5 , 6 ] and in several biological scenarios [ 7 , 8 ]. The collective dynamics of confined colloids can be completely different from that of free colloids: for instance, confined colloids can self-organize into vortex structures [ 9 , 10 ], coherent motion [ 11 ] or different phase behaviors [ 12–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The collective dynamics of confined colloids can be completely different from that of free colloids: for instance, confined colloids can self-organize into vortex structures [ 9 , 10 ], coherent motion [ 11 ] or different phase behaviors [ 12–14 ]. Through the manipulation of functional structure or swarms of confined colloids, microfluidic pumping [ 5 , 15 ], fluid actuation [ 6 ] or solute transport [ 16 ] could be achieved. However, due to the spontaneous and unexpected nature of colloidal suspensions, how to finely tune the collective dynamics of confined colloids remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%